2005
DOI: 10.1007/s00213-005-2196-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of kava-kava extract on the sleep–wake cycle in sleep-disturbed rats

Abstract: Kava-kava extract is an herbal medicine having not only hypnotic effects, but also sleep quality-enhancement effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 21 publications
0
37
0
2
Order By: Relevance
“…It is well known that delta activity is an indicator of depth within non-REM sleep (18 -20). A decrease in delta activity has been also reported for other benzodiazepines, such as triazolam, flunitrazepam and midazolam, during non-REM sleep (17,21,22). From these findings, it became clear that benzodiazepines produced an increase in the quantity of sleep, but the sleep quality deteriorated.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It is well known that delta activity is an indicator of depth within non-REM sleep (18 -20). A decrease in delta activity has been also reported for other benzodiazepines, such as triazolam, flunitrazepam and midazolam, during non-REM sleep (17,21,22). From these findings, it became clear that benzodiazepines produced an increase in the quantity of sleep, but the sleep quality deteriorated.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, it was found that nitrazepam caused a significant decrease in delta activity during non-REM sleep. Delta activity is thought to reflect sleep quality (17). It is well known that delta activity is an indicator of depth within non-REM sleep (18 -20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flunitrazepam had no significant effect on any of the parameters examined, even at the highest dose tested (3 mg/kg). Contrariwise, Shinomiya et al 18) reported that flunitrazepam at 3 mg/ kg caused a decrease in sleep latency, a decrease in wake time, and an increase in non-REM sleep time in rats whose sleep was disturbed by both water-and altitude-induced stress. Flunitrazepam is a benzodiazepine hypnotic that binds to the GABA A receptor and enhances the effect of GABA.…”
Section: Discussionmentioning
confidence: 99%
“…A escolha da banda delta justifica-se pelo fato desta estar relacionada a mecanismos de sono/vigília 1 5 . Estudos com ansiolíticos e ervas usadas para distúrbios do sono, com o Kava Kava, apontam para uma tendência de aumento da banda delta em diversas áreas corticais 11,16 .…”
Section: Métodounclassified